Design of a low-profile wideband spiral antenna - Deng, Wenting (2013)
It is a long time research on designing wide band antennas of low profile that can be used in satellite communications and military systems. Nowadays,the demand for antenna is significantly increased. Spiral antenna is a kind of radio frequency antenna which operates over a wideband frequency and radiates circularly polarizedwave. It can be shaped as single-arm, double-arm, or more arms.